Resource availability underlies the plant‐fungal diversity relationship in a grassland ecosystem. Issue 1 (21st December 2017) - Cline, Lauren C.; Hobbie, Sarah E.; Madritch, Michael D.; Buyarski, Christopher R.; Tilman, David; Cavender‐Bares, Jeannine M.
Abstract: It is commonly assumed that microbial communities are structured by "bottom‐up" ecological forces, although few experimental manipulations have rigorously tested the mechanisms by which resources structure soil communities. We investigated how plant substrate availability might structure fungal communities and belowground processes along an experimental plant richness gradient in a grassland ecosystem. We hypothesized that variation in total plant‐derived substrate inputs, plant functional group diversity, as well as the relative abundance of C4 grasses and legumes would modulate fungal α‐ and β‐diversity and their rates of soil carbon (C) and nitrogen (N) cycling. To test these predictions, we molecularly characterized fungal communities, as well as potential extracellular enzyme activity, net N mineralization, and soil organic matter respiration. We found higher fungal richness was associated with increasing aboveground plant biomass; whereas, fungal β‐diversity was explained by contributions from C4 grass and legume relative dominance, plant functional group diversity, as well as plant biomass. Furthermore, aboveground plant biomass consistently shaped the richness and composition of individual fungal trophic modes (i.e., saprotrophs, symbiotrophs, pathotrophs). Finally, variation in extracellular enzyme activity, net N mineralization rates, and soil organic matter respiration was significantly explained by fungal β‐diversity when fungi were functionally classified. Via changes in the supply and composition of organic substrates entering soil, our study demonstrates that changes in the plant species richness and functional composition collectively influence fungal communities and rates of soil C and N cycling.